Combining sport and academic career: Exploring the current state of student-athletes' dual career research field - Vidal-Vilaplana, A.; Valantine, I.; Staskeviciute-Butiene, I.; González-Serrano, M. H.; Capranica, L.; Calabuig, F. (Journal of Hospitality, Leisure, Sport & Tourism Education, 2022)
Understanding the Dual Career as the process of combining the athletic career with an academic career or work, the main purpose of this paper is to study the current state of research on this reality. Based on this, a review of the scientific literature published in journals indexed on the Web of Science has been performed. This review consists of a bibliometric analysis, which provides basic bibliometric indicators, the co-authorship and keyword networks, and a thematic analysis of the search. Secondly, a systematic review of the most representative documents of each thematic cluster has been carried out. The results indicate that research on Dual Career is in an intermediate state, where there is a growing interest during the last years, and show that Europe is the main focus of research on this reality, despite the need of further research considering non-European terms to refer to this reality. The paper provides an overview of Dual Career research's current state and may serve as a starting point to guide future research, and help education and sport policy makers to develop better measures to facilitate student-athletes` Dual Career.